Fundamentals of planning developing tourism - Kastarlak, Bulent I.; Barber, Brian (Upper Saddle River, NJ, 2012)
Fundamentals of Planning and Developing Tourism brings into focus the growing importance of tourism in developing economies of the world for producing social change, alleviating poverty, and achieving sustained growth. The book grew out of the necessity to organize a quantifiable methodology that employs tourism as a growth agent for planning urban and te gional development. The methodological basis of the book is the BIK System developed by the author from urban and regional planning principles. These principles include, but are no limited to, economics and marketing, which have often been the focus in many previo tourism publications.
Keywords: Tourism-Management; Tourism-Planning